2020
DOI: 10.3390/ijerph17228297
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Resilience, and Well-Being in Italian Children and Their Parents during the COVID-19 Pandemic

Abstract: The novel coronavirus (COVID-19) outbreak has forced parents and children to adopt significant changes in their daily routine, which has been a big challenge for families, with important implications for family stress. In this study, we aimed to analyze the potential risk and protective factors for parents’ and children’s well-being during a potentially traumatic event such as the COVID-19 quarantine. Specifically, we investigated parents’ and children’s well-being, parental stress, and children’s resilience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
215
5
25

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(305 citation statements)
references
References 83 publications
(114 reference statements)
21
215
5
25
Order By: Relevance
“…Regarding children’s psychological well-being, their overall stress level increased compared to the pre-COVID-19 period. This result is in line with recent studies that reflected that children’s worsened stress level and mental health are related to the pandemic [ 42 , 43 , 44 ]. As expected, the sub-areas of children’s stress varied in significance of change.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding children’s psychological well-being, their overall stress level increased compared to the pre-COVID-19 period. This result is in line with recent studies that reflected that children’s worsened stress level and mental health are related to the pandemic [ 42 , 43 , 44 ]. As expected, the sub-areas of children’s stress varied in significance of change.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported a rise in various stress responses and mental health issues during the COVID-19 pandemic [ 12 , 42 , 43 , 44 ], such as higher levels of anxiety symptoms and more prevalent clinical depression symptoms. Existing research, however, mainly focused on behavioral and emotional disorders from the mental health clinicians or pediatrics’ perspectives, resulting in limited evidence regarding children’s everyday stress level during the current pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding some demographic variables, we found higher prosocial behavior among adolescent girls, similar to a study conducted in Italy ( 7 ), where they also found these results among children. Finally, a study in Germany found higher rates of all problems and symptoms assessed by SDQ among children and adolescents coming from low socioeconomic status and of parents with lower education ( 36 ).…”
Section: Discussionsupporting
confidence: 90%
“…Psychological distress related to COVID-19 has been studied in the Italian population [ 14 , 15 ], and the implications of this pandemic for the mental health of young people has been outlined [ 16 , 17 ]. Additionally, the traumatic effects on families of pandemics and of the associated disease-containment measures have been confirmed globally [ 18 , 19 ], highlighting the need to focus on the most vulnerable families [ 20 ]. However, the perspectives of families with a child with a disability are lacking.…”
Section: Introductionmentioning
confidence: 99%